The dead duke, his secret wife, and the missing corpse : an extraordinary Edwardian case of deception and intrigue - Eatwell, Piu Marie (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2015)
"One of the most notorious and bizarre mysteries of the Edwardian age, for readers who loved The Suspicions of Mr. Whicher. At the close of the Victorian era, as now, privacy was power. The extraordinarily wealthy 5th Duke of Portland had a mania for it, hiding in his horsedrawn carriage and creating tunnels between buildings to avoid being seen. So when, in 1897, an elderly widow asked the court to exhume the grave of her late father-in-law, T.C. Druce, under the suspicion that he'd led a double life as the 5th Duke, no one could dismiss her claim. The eccentric duke, Anna Maria was sure, had faked his death as Druce, and, therefore, her son should inherit the Portland millions. A lurid, decade-long case was born. Uncovering new archival treasures and offering a 'lively account of ... the lies, deceit, and hypocrisy of Victorian society' (The Times), Piu Marie Eatwell evokes an era in transition, when the rise of sensationalist media blurred every fact into fiction, and when family secrets and fluid identities pushed class anxieties to new heights"--Provided by publisher.